Effect Of Interactive Video Analysis Training on The Acquisition of Dribbling Skills in Basketball Among Students at College of Physical Education and Sports Sciences Baghdad University - Abdulhussein , Ahmed (Journal of Physical Education, 2025)
This study investigates the effect of interactive video analysis on the acquisition of dribbling skills in basketball among first-year students at the College of Physical Education and Sports Sciences, University of Baghdad. A sample of 50 students was divided into an experimental group (n=25) receiving training with interactive video analysis and a control group (n=25) trained using traditional methods. The Johnson Basketball Dribble Test was administered as pre- and post-tests over an 8-week intervention (December 2024 to April 2025). Results showed significant improvements in both groups, with the experimental group demonstrating greater gains in dribbling speed and accuracy (p < 0.001, Cohen’s d = 1.32). The findings highlight the efficacy of interactive video analysis in providing precise, real-time feedback to enhance motor skill acquisition. The study suggests that technology-enhanced training can improve basketball performance among novice learners, advocating its integration into physical education curricula. Limitations include the focus on dribbling and the short intervention duration, warranting further research on other skills and long-term effects.